Erziehungswissenschaftliche Grundbegriffe im Spiegel der Inklusionsforschung - Sturm, Tanja; Balzer, Nicole; Budde, Jürgen; Hackbarth, Anja (Schriftenreihe der AG Inklusionsforschung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2023)
Education, socialisation - terms like these are constitutive for educational science. What is the significance of these basic concepts within the discourse on inclusion? What impulses can the discourse of inclusion bring to the academic discussion of these terms? Historical, theoretical, methodological and empirical contributions examine the relations between basic concepts in educational science and inclusion research, make problems visible and show their significance in teaching.